THE STUDY OF HYPOGLYCEMIC ACTIVITY OF 3-BENZYL-8-METHYLXANTHINE DERIVATIVES - I. М. Bilay; K. V. Aleksandrova; S. V. Levich; O. S. Shkoda; E. O. Michayluk; D. M. Yurchenko; D. M. Danilchenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2015)
Diabetes mellitus is a chronic endocrine disease. It etiology is the impact of both endogenous (genetic) and exogenous factors that cause absolute or relative shortage of insulin or not effective use of it, which in turn leads to disruption of all kinds of substances exchange. The study of this problem is actual due to the high prevalence of diabetes, chronic disease, the tendency to increase the number of patients, their high morbidity and mortality. Diabetes is characterized by high blood glucose levels, which eventually leads to various complications associated with many human systems damage. Hormones (insulin and its analogues) and synthetic drugs (sulfonylureas, biguanides etc.) are used For the treatment of diabetes, but their high toxicity, cumulativeness, various side effects (autoimmunization, cutaneous allergic reactions, disturbance of the micro flora of the digestive tract), and the formation of insulin resistance restrict the use of these drugs in clinical practice. On this aspect the attention of researchers is attracted to xanthine derivatives, which are known as substances with wide range of biological activities including hypoglycemic.